桃子腳課程密碼 Curriculum Code in Tur Ya Kar - 周仁尹 Jen-Yi Chou (Higher Education Foundation, 2019)
桃子腳國民中小學位於新北市北大特定區，採無圍牆開放式校園設計，佐以對生態環境尊重的綠建築，與社區深度連結的濃厚地方文史情感，蘊含豐富的美學能量與藝術品味，成就出適性發展、多元學習、豐富人文涵養的校園美學文化，發展出十項校園密碼。校園密碼即課程發展，如桃子腳校園特有的植物染課程，本文以在地文化情染為例，說明桃子腳的課程密碼。 New Taipei Municipal Tur Ya Kar Elementary & Junior High School is located in the Taipei University Special District in New Taipei City. The school is characterized by its fenceless campus and green buildings, with which the school aims to show its respect to the environment and a strong cultural and historical connection with the community. Also, the unique aesthetic sense and artistic taste embodied in the design of the campus help creat a learning environment for the students to nurture their talents with diversed abilities, promote their adaptive developments and enrich their humanitic cultivation. The aesthetic culture in the campus so far has helped develop the ten campus codes and the unique plant dyeing course, which not only exemplifi es a school-based course but also reflects its care for the local culture.